Problems of definition "will" and "willability" in civil law of Ukraine - Демчук, Антон Михайлович; Demchuk, Anton M. (Paneurópska vysoká škola, Fakulta práva, 2015)
One of the main requirements of transaction is the fact, that the will of the user must be free and meet its internal freedom. The existence of different defects of will are the basis for nullity in court (for example, mistake, fraud, violence, coincidence of serious circumstances etc.) according to provisions of the Civil Code of Ukraine. Practice of consideration these cases about recognition of transactions void discovers ambiguity of some legislative provisions, which establish the legal consequences of the invalidity transactions with will defects. So the courts apply the same rule of substantive law ambiguously in disputes that follow from such relationships. The judicial practice not fully solves this problem which is defined in the explanation of high specialized courts.
Keywords: willability; will